Performance of vision language models for optic disc swelling identification on fundus photographs - Kelvin Zhenghao Li; Kelvin Zhenghao Li; Kelvin Zhenghao Li; Tuyet Thao Nguyen; Tuyet Thao Nguyen; Heather E. Moss; Heather E. Moss (Frontiers in Digital Health)
IntroductionVision language models (VLMs) combine image analysis capabilities with large language models (LLMs). Because of their multimodal capabilities, VLMs offer a clinical advantage over image classification models for the diagnosis of optic disc swelling by allowing a consideration of clinical context. In this study, we compare the performance of non-specialty-trained VLMs with different prompts in the classification of optic disc swelling on fundus photographs.MethodsA diagnostic test accuracy study was conducted utilizing an open-sourced dataset. Five different prompts (increasing in context) were used with each of five different VLMs (Llama 3.2-vision, LLaVA-Med, LLaVA, GPT-4o, and DeepSeek-4V), resulting in 25 prompt-model pairs. The performance of VLMs in classifying photographs with and without optic disc swelling was measured using Youden's index (YI), F1 score, and accuracy rate.ResultsA total of 779 images of normal optic discs and 295 images of swollen discs were obtained from an open-source image database. Among the 25 prompt-model pairs, valid response rates ranged from 7.8% to 100% (median 93.6%). Diagnostic performance ranged from YI: 0.00 to 0.231 (median 0.042), F1 score: 0.00 to 0.716 (median 0.401), and accuracy rate: 27.5 to 70.5% (median 58.8%). The best-performing prompt-model pair was GPT-4o with role-playing with Chain-of-Thought and few-shot prompting. On average, Llama 3.2-vision performed the best (average YI across prompts 0.181). There was no consistent relationship between the amount of information given in the prompt and the model performance.ConclusionsNon-specialty-trained VLMs could classify photographs of swollen and normal optic discs better than chance, with performance varying by model. Increasing prompt complexity did not consistently improve performance. Specialty-specific VLMs may be necessary to improve ophthalmic image analysis performance.